Herpes simplex infection as possible etiology for febrile neutropenia and mucositis in patients treated for hematological malignancies - Kubesová, H; Penka, M; Král, Z; Adam, Z; Vásová, I; Tomíska, M; Vorlícek, J (Acta medica Austriaca, 1998)
Mucositis is a common complication following chemotherapy. Clinical findings similar to herpetic infection are observed in some patients. Acyclovir administered in addition to empirical, antibiotic treatment improves the course of mucositis, and can also bring down the temperature. The aim of our study was to define the etiological influence of herpetic infection on the course of febrile neutropenia in patients with mucositis. A total of 34 patients with febrile neutropenia were divided into 2 groups: 15 with typical herpetic eruption, and 19 with non-specific mucositis. Both groups received 5-10 mg/kg acyclovir every eight hours together with empiric antibiotic treatment. The effect of acyclovir was studied, and results compared in the two patient groups. Body temperatures decreased in both groups, clinical symptoms, however, disappeared more slowly in the group with non-specific mucositis. The beneficial effect of acyclovir treatment was particularly well expressed in seropositive patients. In this group of patients, herpetic infections may recur under further chemotherapy. Thus, it would be useful to administer acyclovir to them prophylactically during risk periods.
Keywords: senioři; diferenciální diagnóza; neutropenie; herpes simplex; Neutropenia; hematologické nádory; Retrospective Studies; Opportunistic Infections; Herpes Simplex; Middle Aged; Hematologic Neoplasms; mužské pohlaví; antivirové látky; Adult; stomatitida; oportunní infekce; aktivace viru; Stomatitis; ženské pohlaví; Acyclovir; retrospektivní studie; Humans; acyklovir; horečka neznámého původu; lidé středního věku; Fever of Unknown Origin; Diagnosis, Differential; dospělí; Antiviral Agents; Female; Aged; Virus Activation; lidé; Male